ANALISIS KONTRASTIF PRONOMINA BAHASA MUSI DENGAN BAHASA INDONESIA - Shelty, Okta; Puspita, Yenny; Nufus, Hayatun (Universitas PGRI Palembang, 2023)
Contrastive analysis of Musi language pronouns with Indonesian is the activity of comparing elements contained in two or more languages to find out the similarities and differences of these elements. The problem in this study is how to analyze the contrastive pronouns of the Musi language with Indonesian. The purpose of this study is to know and describe the differences between Musi language pronouns and Indonesian. Keywords : Contrastive, pronouns, and Musi language